A Pragmatic Analysis of Presuppositions In Moana 2 - Siagian, Claudya Benesa; Hutauruk, Bertaria Sohnata; Purba, Rudiarman (Dharmas Education Journal (DE_Journal), 2025)
This study aims to identify the types of presuppositions found in the speech of the characters in the movie Moana 2 and describe the meaning of presuppositions in the transcript of the movie. The approach used is qualitative research with descriptive method and data analysis technique which includes steps: Organizing and Familiarizing, Coding and Reducing, and Interpreting and Representing. The data of this study are the speech of Moana, Maui, and three other crew members, Kele, Moni, and Loto in the Moana 2 script that contain presumptions. The theory of presumption used is Yule's theory, which includes Existential Presumption, Factive Presumption, Lexical Presumption, Structural Presumption, Non-Factive Presumption, and Counter-Factual Presumption. The results of data analysis show that there are five types of presumption in the movie script, with existential presumption being the most dominant type, which is 44% of the total 34 data. Furthermore, structural presumption is found as much as 23%, followed by factive presumption 15%, lexical presumption 9%, and counterfactual presumption 9%. This research provides an understanding of the use of presupposition in movie speech and its contribution in constructing meaning.